Contextualizing the Archaeological Landscape of Kamakhya Temple in the Light of Material Evidences - Tamta, Priyanka (My University, 2019)
The archaeological site of Kamakhya is a living temple of Goddess Kamakhya who is worshipped in a non-anthropomorphic form as a yoni (vulva) with no physical manifestation along with the Dashamahavidyas. The present study has attempted to understand the evolution of the archaeological site of Kamakhya temple with the help of material evidences left on the site in the form of its art and architecture. Understanding the context behind the material evidence can help us in understanding the process of site selection and settlement pattern. Further, making this evidence a readable text, which is easy to decipher, offers access to understanding past settlements and their way of life. The present study has used three theoretical approaches, Landscape archaeology, Sacred geography and Contextual approach to answer the following questions: 1) The prime factors behind the development of the site; 2) type of archaeological records created during the 1516 years of habitational history of the site; 3) the processes through which such archaeological records were created. We have used the archaeological survey methods and scientific methods (XRD, Thin Section Petrography, FE-SEM, EDX and Micro-optical analysis) for studying the archaeological site of Kamakhya temple. From the study, we have successfully identified five different phases of temple building activity from the 5th century A.D. to the 21st century. On the basis of architectural fragments of kalasha, urushringa and amalaka scattered across the site, the first stone temples were built in Nagara Hindu temple architecture style with prominent curvilinear sikhara (tower) and urushringa (subsidiary sikhara). Evidence of the brick temples constructed on the already existing stone ‘adhisthana’ marked the evolution of a hybrid form of architecture known as Nilachala temple architecture famous for its bulbous polygonal dome with minarets or small side domes inspired by the Bengali temple architecture. We also found through sculptural documentation that majority of the Kamakhya sculptures belong to the Medieval Kamarupa School of Art. Further, three types of stone used for making sculptures and temples have been identified on the site. They are a) Granite, b) Sandstone and c) Basalt. The results of the present study can be utilized as a reference base for understanding the temporal changes in the archaeological site of Kamakhya and its art and architecture.
Sharma, Sukanya
Keywords: HUMANITIES AND SOCIAL SCIENCES